Narrative-Based Assessment: Using Student Stories for Measuring Learning Progress and Metacognition - Siri Lek; Ming Pong; Ravi Dara; Widiharto Purnomo (International Journal of Educational Narratives, 2026)
Background. Narrative-based assessment has emerged as an alternative approach to traditional evaluation practices that often prioritize standardized outcomes over learning processes. Conventional assessments provide limited insight into how students develop understanding and regulate their thinking. Student narratives, in contrast, offer rich representations of learning experiences and reflective engagement, yet their systematic use for measuring learning progress and metacognition remains underexplored. Purpose. This study aims to examine how narrative-based assessment using student stories can be utilized to measure learning progress and metacognitive development. The research seeks to identify narrative features that indicate cognitive growth, reflective depth, and self-regulatory awareness in learning contexts. Method. A qualitative descriptive research design with a longitudinal narrative approach was employed. Participants were students engaged in reflective learning activities selected through purposive sampling. Data were collected through student narratives, reflective prompts, and learning artifacts, and analyzed using thematic, structural, and linguistic analysis to identify indicators of learning progress and metacognition. Results. Findings indicate that repeated narrative engagement leads to increased metacognitive awareness, strategy articulation, and evaluative reflection. Student stories demonstrated progressive development from descriptive accounts toward coherent and self-regulated learning narratives. Case analysis further illustrated individual learning transformation through narrative expression. Conclusion. Narrative-based assessment is effective for capturing learning progress and metacognition as dynamic and developmental processes. The novelty of this study lies in operationalizing student narratives as systematic assessment evidence, positioning storytelling as a valid and inclusive approach for measuring learning development.